(untitled) (مجلة جامعة اللاذقية- سلسلة العلوم البيولوجية, 2019)
جُمعت عينات القشري برغوث الماء العذب 1820 Daphnia magna Straus من أحد المصادر المائية العذبة القريبة ( سد بكسا - اللاذقية )، فضلاً عن عينات من منطقة الهبيط التابعة لمحافظة إدلب. تمت أقلمة هذه الكائنات لفترة محددة في المخبر قبل إجراء الدراسات البيولوجية عليها . ثم بعد ذلك أجريت العديد من التجارب المختبرية تتضمن دراسة تطورها, و سرعة نموها الطولي والوزني، وتكاثرها وخصوبتها ومدة حياة الإناث البكرية في شروط مغذية مختلفة . بدأت التجارب من 01 / 4 / 2008 ولغاية22 / 7 /2008 بهدف تحديد شروط الأوساط المغذية المثلى لاستزراع أفراد النوع D. magna بوصفه غذاءً حياً ليرقات وصغار الأسماك الاقتصادية. بينت التجارب أن سرعة النمو الطولي والوزني متباينة تبعاً لتركيز الأوساط المغذية، كما سجلت القيم العظمى لهذه السرعة من زمن الفقس حتى مرحلة النضج الجنسي. وتبين من النتائج أيضاً أن أفضل الأوساط المغذية لاستزراع أفراد هذا النوع تحت الشروط المختبرية كان في وسط خليط من الطحالب الخضراء. The specimens of Daphnia magna Straus 1820 have been collected from the nearest freshwater reservoir (BAKSSA - Lattakia) in addition to specimens collected from a freshwater pond (AL- Habeet area – Idleb). The organisms under investigation have been acclimatized to laboratory-testing conditions before proper biological studies have been made. Afterwards, a number of experiments have been conducted concerning the speed of its longitudinal and weight growth, egg production, and the total life span of female parthenogenesis under various nutritional conditions. Experiments have started from 1/04/2008 through 22/07/2008 in order to define the best nutritional conditions to cultivate D. magna as food for fish organisms. The experiments showed that the rate of the longitudinal and weight growth is varied according to nutritional concentration media. It was also observed that the speed of growth reaches its utmost from hatching till adulthood. It has also been noticed that the best nutritional media to cultivate D. magna under experimental conditions were found to be a mixture of green algae.